2021
DOI: 10.3390/s21144803
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Pear Fruit Detection and Counting Using YOLOv4 Models and Deep SORT

Abstract: This study aimed to produce a robust real-time pear fruit counter for mobile applications using only RGB data, the variants of the state-of-the-art object detection model YOLOv4, and the multiple object-tracking algorithm Deep SORT. This study also provided a systematic and pragmatic methodology for choosing the most suitable model for a desired application in agricultural sciences. In terms of accuracy, YOLOv4-CSP was observed as the optimal model, with an AP@0.50 of 98%. In terms of speed and computational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 41 publications
(53 reference statements)
0
48
0
3
Order By: Relevance
“…In [12] the authors propose to produce a real-time pear counter system for mobile applications using RGB video and the variants of the YOLOv4 object detector model and the multiple object-tracking algorithm Deep SORT, obtaining an accuracy of 98% with a AP@0.50 with YOLOv4-CSP. They obtained better computational cost and speed with YOLOv4-tiny, concluding that the best model is the YOLOv4 in accuracy and speed.…”
Section: Scientific Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [12] the authors propose to produce a real-time pear counter system for mobile applications using RGB video and the variants of the YOLOv4 object detector model and the multiple object-tracking algorithm Deep SORT, obtaining an accuracy of 98% with a AP@0.50 with YOLOv4-CSP. They obtained better computational cost and speed with YOLOv4-tiny, concluding that the best model is the YOLOv4 in accuracy and speed.…”
Section: Scientific Publicationsmentioning
confidence: 99%
“…Parico et al [12] RGB video YOLOv4, YOLOv4-CSP, YOLOv4-tiny. Nasirahmadi et al [13] RGB video YOLO v4, R-FCN and Faster R-CNN Wang et al [14] RGB video YOLOv3…”
Section: Article Data Type Modelmentioning
confidence: 99%
“…In a citrus detection study, a YOLO v4 model was able to detect the fruit with an accuracy of 96% using a Kinect v2 camera. In another study, pear fruit detection and counting using different YOLO v4 models (i.e., YOLO v4, YOLO v4-CSP, YOLO v4-tiny) resulted in achieved average precision of 98% [35]. Furthermore, [31] reported that YOLO v4 was able to detect apple fruit in a complex environment with recall and an average precision of around 93 and 88%, respectively, compared to Faster R-CNN with 90 and 83%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The average apple detection time was 19ms with FPR at 7.8% and FNR at 9.2% using YOLOv3 and with FPR at 3.5% and FNR at 2.8% using YOLOv5 [12]. Parico and Ahamed proposed a real-time pear fruit counter using YOLOv4 and DeepSORT, with an AP@0.50 of 98% [13]. Yan et al proposed a light-weight fruit target real-time detection method for the apple picking robot based on improved YOLOv5, with an mAP of 86.75% [14].…”
Section: Introductionmentioning
confidence: 99%